Democratic disunity rhetorical tribalism in 2020 - Kelley, Colleen Elizabeth (Lexington studies in political communication., 2022)
"Democratic Disunity: Rhetorical Tribalism in 2020 maintains that while attention has focused on the tribal bifurcation of the GOP, the Democratic Party is similarly divided. Rhetorical strategies anchored in dialogue may diminish the effect of political partisanship, including its toxic variations between and within American political parties"--